Relation between levels of anxiety and coping strategies in Colombian university (2011)
This study is not experimental, correlational, analyzes the relationship between anxiety levels and coping strategies most used by students who begin their internship in psychology at the Pedagogical and Technological University of Colombia, the population is composed of 36 young students with an age range between 21 and 29, unmarried, who do their internship during the second half of 2010, the instruments used are the Coping Strategies Scale Chorot and Sandin (1993) validated for Colombian population by Londoño Henao, Puerta, Posada, Arango, & Aguirre (2006) and Zung of Zung scale (1971) validated and adapted for Colombia by De la Ossa, Martinez & Herazo (2009). Analysis of results from the Pearson correlation coefficient and the statistical package SPSS version 17.0, show that a high negative correlation between anxiety level 1 (no anxiety) and the strategy problem solving and cognitive avoidance, while Level 3 (moderate to severe) is positively correlated with cognitive avoidance strategy.